Startling temperature effect on proteins when confined: single molecular level behaviour of human serum albumin in a reverse micelle. Issue 21 (11th May 2016) - Sengupta, Bhaswati; Yadav, Rajeev; Sen, Pratik
Abstract : The present work reports the effect of confinement, and temperature therein, on the conformational fluctuation dynamics of domain-I of human serum albumin (HSA) by fluorescence correlation spectroscopy (FCS). Abstract : The present work reports the effect of confinement, and temperature therein, on the conformational fluctuation dynamics of domain-I of human serum albumin (HSA) by fluorescence correlation spectroscopy (FCS). The water-pool of a sodium bis(2-ethylhexyl)sulfosuccinate (AOT) reverse micelle has been used as the confined environment. It was observed that the conformational fluctuation time is about 6 times smaller compared to bulk medium when confined in a water-pool of 3.5 nm radius. On increasing the size of the water-pool the conformational fluctuation time was found to increase monotonically and approaches the bulk value. The effect of confinement is on par with the general belief about the restricted motion of a macromolecule upon confinement. However, the effect of temperature was found to be surprising. An increase in the temperature from 298 K to 313 K induces a larger change in the conformational fluctuation time in HSA, when confined. In the bulk medium, apparently there is no change in the conformational fluctuation time in the aforementioned temperature range, whereas, when HSA is present in an AOT water-pool of radius 3.5 nm, about an 88% increase in the fluctuation time was observed. The observed prominent thermal effect on the conformational dynamics of domain-I of HSA in the water-pool of an AOT reverse micelle as compared to in the bulk medium was concluded to arise from the confined solvent effect.